2020
DOI: 10.1021/acsomega.0c01219
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction and Removal of Cadmium Ions over Bentonite Clay-Supported Zinc Oxide Microcubes in an Aqueous Solution

Abstract: Cadmium ion is toxic to organisms and shows persistence because of its nondegradability. Photoreduction of the cadmium ion (Cd­(II)) was studied using a bentonite-supported Zn oxide (ZnO/BT) photocatalyst in an aqueous medium under ultraviolet light. The prepared ZnO/BT photocatalyst was characterized by diffuse reflectance spectroscopy, field-emission scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, photoluminescence spectroscopy, transmission electron microscopy, ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…The solution was quickly taken out for filtration at a predetermined time to determine the mass concentration of Cd (II) in the solution. As mentioned by Hossein et al, on increasing pH from 4 to 7, the percent of photoreduction decreased . It is suggested that the photoreduction of the metallic cation is significantly dependent on their tendency toward the hydrolysis reaction. ,, …”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…The solution was quickly taken out for filtration at a predetermined time to determine the mass concentration of Cd (II) in the solution. As mentioned by Hossein et al, on increasing pH from 4 to 7, the percent of photoreduction decreased . It is suggested that the photoreduction of the metallic cation is significantly dependent on their tendency toward the hydrolysis reaction. ,, …”
Section: Methodsmentioning
confidence: 84%
“…Heavy metals such as lead, mercury, cadmium, nickel, and chromium are found in the wastewater of various industries such as mining, petrochemicals, pharmaceuticals, plastic products, paper, and fabric dyeing. Because of the adverse effects of heavy metals, many of their derivatives are classified as pollutants . Penetration of heavy metals inside the body leads to various adverse effects and also many diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon loading ZnO on the porous carbon framework (middle), new vibration bands appeared at 1041, 901, 719, and 468 cm −1 . 54 They corresponded to asymmetrical and symmetrical Zn–O stretching vibrations. As compared to APC, the OH peak was broadened, indicating that the number of OH increased following the impregnation process, and the intensity peak of the CO band was enhanced due to the overlap with the chloride anions derived from the unreacted precursor.…”
Section: Resultsmentioning
confidence: 99%
“…This process can activate and undertake both oxidation and reduction reactions under irradiation of light energy [23]. By conducting this method for the metal ion treatment, especially in the removal of Cd(II), this heavy metals would be directly reduced from its toxic ionic phase (Cd(II)) into non-toxic metallic phase (Cd(0)) [24][25][26]. It is believed that the photocatalytic method for the removal of heavy metals pollutants is more green, clean and economical than the conventional methods [27,28].…”
Section: Introductionmentioning
confidence: 99%